Resepsi Masyarakat Adat Talang Mamak atas Modernisasi melalui Program Pemberdayaan Komunitas Adat Terpencil di Indragiri Hulu, Riau - Ansor, Muhammad; Masyhur, Laila Sari (Samudra Publisher, 2024)
This article discusses the Talang Mamak people's reaction to the government's modernization and development through the empowerment program for remote indigenous communities in the Indragiri Hulu Province of Riau. The author argues that the government's good intentions to modernize remote indigenous communities are part of an effort to advance and modernize them, not fully realized as expected. This writing uses qualitative methodology. We obtain research data sources from a combination of field research and library research institutions. We conduct field observations and in-depth interviews with selected Talang Mamak individuals. We utilize the research library to access articles from scientific journals, books, magazines, newspapers, and other relevant documents related to the research topic. This writing suggests that Talang Mamak's empowerment program for remote indigenous communities has received a positive religious reception. They generally welcomed the program, although they were critical and partly rejected. Some of them see education as a way to improve the situation, even though they realize that their resources are still scarce. They expect the government to do something to improve their economic conditions. The Mamak Talang people need the country to restore the economic, social, and cultural ecosystems that have suffered damage as a result of companies operating around their living environment.